Distribution and Association of ABO and Rh Blood Group Antigens with BMI Among Nepalese and Indian Students Studied in a Medical College of Nepal - Kar, Kalipada; Kar, Sujata (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Blood group antigens and body mass index of human are gaining importance for many diseases. Some attempts were reported to find any relationship between BMI and Blood groups with some contradictions. The possible association between BMI and blood groups of Nepalese and Indian medical students is yet to be established. Methods: Blood groups, ABO and Rh systems and body mass index (BMI) of participants, medical students of Nepalese and Indian origin were determined and analyzed statistically. Results: The distribution frequencies of 10.56%, 17.08%, 3.06%, and 20.28% females and 9.03%, 16.39%, 3.61% and 20.0% males of both the countries were present in A, B, AB and O blood groups, respectively. Rh-negative participants were predominantly present in O blood group. The observed frequencies of participants with different BMI group were distributed as 56.11%, 24.72%, 10.69% and 8.47% in Normal, Overweight, Underweight and Obese groups, respectively. Underweight participants were prevalent in O group and in females. The difference between the distribution of Nepalese females and males with Normal BMI was found significant in A and O. A distribution pattern of B>O>A>AB was observed for Overweight group. The occurrence of Obese is few folds higher among Indian participants than Nepalese and prevalent in males. Obese participants were found more associated with B and O blood group. Conclusions: Participants with A were more prevalent among Nepalese in respect to Indian. Rh-negative participants were distributed as 1.67% and 5.0% in Nepalese and Indians, respectively and predominantly present in O (4.44%) and are more prevalent in Indian males. In Normal BMI Nepalese were significantly more as compared to Indians. In the Underweight group females were significantly more prevalent as compared to males and found maximally associated with O blood group and most of them are Nepalese. In Overweight group males were more than females. Participants with obesity were mostly present in B and O blood group and most of them are Indian.